X+3/2x=45

Simple and best practice solution for X+3/2x=45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+3/2x=45 equation:



X+3/2X=45
We move all terms to the left:
X+3/2X-(45)=0
Domain of the equation: 2X!=0
X!=0/2
X!=0
X∈R
We multiply all the terms by the denominator
X*2X-45*2X+3=0
Wy multiply elements
2X^2-90X+3=0
a = 2; b = -90; c = +3;
Δ = b2-4ac
Δ = -902-4·2·3
Δ = 8076
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{8076}=\sqrt{4*2019}=\sqrt{4}*\sqrt{2019}=2\sqrt{2019}$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-90)-2\sqrt{2019}}{2*2}=\frac{90-2\sqrt{2019}}{4} $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-90)+2\sqrt{2019}}{2*2}=\frac{90+2\sqrt{2019}}{4} $

See similar equations:

| h/6{-1}=-3 | | 18=2c−-6 | | 12=(-7x)-9 | | 5x+13=10x-67 | | z/3+18=16 | | -228x(2+3=0 | | z3+ 18=16 | | -10y=5* | | (x-5)^2=15 | | 12y=3* | | 2x+10=x-989 | | 12¥=3x | | 0.95^x=0/5 | | -2=-2(x+3 | | 2x-5=-4+x | | 5x-75=2x+30 | | n2+4n=0 | | x+74=85 | | 45x+89=160 | | 2/3(3x-6)=18 | | 40x+40=160 | | 20x+20=160 | | 18x=6x+x(x-13) | | 5c+5=−12 | | 4.75x+11=6.8x+2.8 | | 4(-1)³+3(-1)²-4(-1)=k | | (4x+2)-6=8 | | 6(x-5)=17 | | -8m-27=5m-(-1-m) | | -3(1+5b)+6=-36-2b | | |7x-20|=|4x+9| | | 8a-4+4a+76=180 |

Equations solver categories